TERRITORIAL DISPUTES BETWEEN RUSSIA AND NEIGHBORING COUNTRIES. COMPARATIVE ANALYSIS - Aleksander Nikolaevich Kharybin (Science and Innovation Center Publishing House, 2018)
The article gives a brief analysis of Russia’s territorial disputes, the author notes that territorial disputes and conflicts affect almost all sections of the border: there are no territorial problems only on the border with Belarus, South Ossetia and Mongolia. Practical recommendations are given to optimize Russia’s foreign policy, as well as scenarios of the most probable development of the situation. By the method of comparative analysis, the author notes the common features of all the disputes on the Russian border: in all problem points, either the status quo is preserved or concessions have been made by Russia, in most cases the disputed territory is under the jurisdiction of Russia, with most of the states there is no border treaty. In situations where the contract is concluded, this also in many cases does not cease the territorial dispute; in most of the disputes, the active role of the United States is seen as an actor of destabilizing the situation.